Abu Terbang (Fly Ash) Sebagai Bahan Tambah Untuk Meningkatkan Kuat Tekan Bata Beton (Paving Block) - Gathot Heri Sudibyo; Yanuar Haryanto; Fatkhurrozak Fatkhurrozak (Jenderal Soedirman University, 2008)
This research was aimed to know the influence of fly ash addition at paving block stress strength. Variation of fly ash was 0%, 20%, 40%, 60%, and 80% from weight of cement with water cement ratio 0,25. The speciment was hexagonal and cube with the comparison 1 cement : 6 sand. The result showed that the stress strength of hexagonal paving block at 56 days with fly ash 20%, 40%, 60% and 80% was increase to 37,166% (7,057 MPa), 18,248% (3,465 MPa), 8.110% (1,54 MPa), and 14,193% (2,695 MPa). The cubic paving block at 56 days with fly ash 20%, 40%, 60% and 80% was increase to 35,932% (5,969 MPa),15,135% (2,514 MPa), 9,534% (1,584 MPa), and 8,318% (1,382 MPa).